Aplicación de contabilidad de cooperativas en la "Cooperativa de taxis Ciudad de Mercadillo”, en la ciudad de Loja, periodo: noviembre-diciembre/2015 - Castro Ochoa, José Luis (2017)
The research entitled "APPLICATION OF ACCOUNTING OF COOPERATIVE IN THE 'COOPERATIVE TAXIS CITY MARKET" IN THE CITY OF LOJA, PERIOD: NOVEMBER-DECEMBER / 2015 "allowed to implement an accounting system for Taxi Cooperative City Market and its contribution administrative and economic improvement of the entity based on the application of accounting standards and accounting procedures established. With the application of accounting cooperatives to the aforementioned company compliance is given to the overall objective and specific objectives are met when performing the inventory of property values, rights and obligations of the cooperative; to shape the plan and manual Union accounts in accordance with the provisions of Resolution No. SEPS-INEPS-2012-0024, the Superintendency of Popular and Solidarity Economy; forms and records to control financial and economic activities are designed. Finally the initial inventory is made to the presentation of financial statements. The development of the accounting process began with the verification of the source documentation to proceed to record transactions, papers and auxiliaries, account balances became known, was presented the trial balance, the worksheet, adjustments and financial information . Financial information that validates the timely and actual decisions, of course under the criteria of the standard and current accounting practice.